Can role model women in politics help married women reduce suicides? Evidence from a quasi-experimental study in Brazil - Arvate, Gabriela Gerote; Arvate, Paulo; Massuda, Adriano; Massuda, Raffael; Atun, Rifat (Frontiers in Public Health, 2025)
BackgroundThe medical literature has demonstrated that macro-variables and social factors can influence suicide rates. Additionally, social science literature has shown that women in prominent political positions (such as mayors) can influence the behavior of other women. The purpose of our work is to demonstrate that women in such positions reduce suicide rates within a group affected by gender inequality: married women.MethodologyWe use regression discontinuity methodology and quasi-experimental electoral designs (elections with a margin of victory very close to zero) to ensure causal inference between the election of women and suicide rates among married women.Principal findingsMunicipalities that elected women as mayors have 1.33 fewer suicides among married women per 100,000 inhabitants compared to those that elected men as mayors.ConclusionThese results offer new insights into how empowered women can challenge social norms and improve public health outcomes.